LEARNING STYLES ON ELEMENTARY STUDENTS' LEARNING OUTCOMES IN THE HUMAN RESPIRATORY SYSTEM USING CONVENTIONAL TEACHING METHODS - Wahyu Noor Aryfien; Idam Ragil Widianto Atmojo; Matsuri Matsuri (Universitas Majalengka, 2025)
Students are less interested in the complicated content on the human respiratory system that is taught using traditional methods. Students' learning outcomes are impacted by traditional instruction that ignores learning style. This research aims to analyze the influence of learning styles on the learning outcomes of fifth-grade elementary school students on the topic of the human respiratory system. The method used in this study is an analytical design with a cross-sectional approach. This study involved 34 fifth-grade students from SDN X and SDN Y in Bulukerto District. The researcher identified learning styles through a modified questionnaire and learning outcomes through optional evaluation questions according to the learning styles. There are 12 people with a visual learning style, 13 people with an auditory learning style, and 9 people with a kinesthetic learning style. The audio learning style having the highest average at 73.46, the kinesthetic learning style at 68.33, and the visual learning style at 67.5. There is no statistically significant difference in the average scores of the three learning styles (p-value=0.391). The findings of this research indicate that conventional learning is more effective for auditory learning styles and can still be used for visual learning. To facilitate all learning styles, the development of interactive multimedia for the human respiratory system material is necessary. Future research should increase the sample size using experimental research and control external factors.